GAMBARAN RESILIENSI IBU YANG MEMILIKI ANAK AUTIS DI TAMAN PELATIHAN HARAPAN MAKASSAR - Beatrix Edyta; Eka Damayanti (Jurnal Biotek, 2016)
This research is a qualitative research that aims to reveal the resilience of mothers of children with autism. Resilience in this study is understood as a capability that is owned by a mother to rise from unpleasant conditions and survive in the face of life's difficulties. Subjects in this study were three mothers in the Taman Pelatihan Harapan youngest child who has autism. Data collected by observation and interview.The results showed that all three subjects experienced different dynamics in each aspect of resilience (emotional control, impulse control, optimistic, analysis of the causes of the problem, empathy, self-efficacy, and increase the positive aspects). Three subjects were surprised, slumped, and did not think their child will have autism disorders. But they are able to accept the conditions and able to bounce back and always think positive future their children will be better. They feel confident to provide the best for his son while trying to figure out and improve their skills in dealing with children, as well as involved in the therapeutic process. Of the three subjects, one of which is able to analyze the causes of the disorder owned so he did not turn himself and others for any inconvenience experienced by children. In addition, one of the factors that support individuals to become resilient is a factor of religiosity. This is shown by the three subjects that always surrender to Allah SWT and gratitude that can make them rise from adversity.